Diagnosis of ULF Wave‐Particle Interactions With Megaelectron Volt Electrons: The Importance of Ultrahigh‐Resolution Energy Channels. Issue 20 (25th October 2018) - Hartinger, M. D.; Claudepierre, S. G.; Turner, D. L.; Reeves, G. D.; Breneman, A.; Mann, I. R.; Peek, T.; Chang, E.; Blake, J. B.; Fennell, J. F.; O'Brien, T. P.; Looper, M. D.
Abstract: Electron flux measurements are an important diagnostic for interactions between ultralow‐frequency (ULF) waves and relativistic (∼1 MeV) electrons. Since measurements are collected by particle detectors with finite energy channel width, they are affected by a phase mixing process that can obscure these interactions. We demonstrate that ultrahigh‐resolution electron measurements from the Magnetic Electron Ion Spectrometer on the Van Allen Probes mission—obtained using a data product that improves the energy resolution by roughly an order of magnitude—are crucial for understanding ULF wave‐particle interactions. In particular, the ultrahigh‐resolution measurements reveal a range of complex dynamics that cannot be resolved by standard measurements. Furthermore, the standard measurements provide estimates for the ULF flux modulation amplitude, period, and phase that may not be representative of true flux modulations, potentially leading to ambiguous conclusions concerning electron dynamics. Plain Language Summary: Plasma waves with periods of a few minutes interact with high‐energy electrons in the near‐Earth space environment. Understanding how the waves affect the electrons is important, as these electrons can potentially damage orbiting satellites. However, these interactions are obscured by a process known as phase mixing where electrons with different energies behave differently yet are mixed together in measurements that have finite energy resolution. We show how a unique data set obtained from National Aeronautics and Space Administration's Van Allen Probes mission can dramatically increase the energy resolution, revealing a range of interactions that are obscured by measurements with lower energy resolution. Key Points: Previous electron measurements could not resolve many energy‐dependent ULF wave interactions with >∼1 MeV electrons due to phase mixing MagEIS histogram channels resolve many interactions: dE/E of 2‐3% compared to standard 20‐30% that is already considered high resolution Without ultrahigh‐resolution measurements, ambiguous conclusions may be reached concerning >∼1 MeV electron dynamics (e.g., drift resonance)